DEPENDÊNCIA DE INTERNET, ANSIEDADE, DEPRESSÃO E USO DE SUBSTÂNCIAS PSICOATIVAS NA ADOLESCÊNCIA TARDIA - Bueno, George Nunes (2020)
With the increased use of the Internet and new technologies, mainly (or among) younger individuals, it can be seen that adolescents demonstrate a pattern of intense use, spending more and more time daily connected and also using social networks. The Inter